2005
DOI: 10.1111/j.0030-1299.2005.14049.x
|View full text |Cite
|
Sign up to set email alerts
|

Are you what you eat? Physiological constraints on organismal stoichiometry in an elementally imbalanced world

Abstract: 2005. Are you what you eat? Physiological constraints on organismal stoichiometry in an elementally imbalanced world. Á/ Oikos 109: 18 Á/28.The relative supply of energy and elements available to organisms in the environment has strong effects on their physiology, which, in turn, can alter important ecological processes. Here we consider how resource imbalances affect three basic physiological processes common to all organisms: elemental uptake, incorporation, and release. We review recent research that addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
265
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 257 publications
(269 citation statements)
references
References 125 publications
(156 reference statements)
2
265
0
2
Order By: Relevance
“…Plant stoichiometry varies with growth rate and the surrounding environment (Ågren and Weih, 2012). Stoichiometric homeostatic regulation reflects underlying physiological and biochemical allocations as organisms respond to their surrounding environments (Hessen et al, 2004) and thus the degree of homeostasis may be highly relevant to fitness and to a species' ecological strategy on the one hand (Frost et al, 2005) and to recycling processes of superfluous material on the other one (Meunier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Plant stoichiometry varies with growth rate and the surrounding environment (Ågren and Weih, 2012). Stoichiometric homeostatic regulation reflects underlying physiological and biochemical allocations as organisms respond to their surrounding environments (Hessen et al, 2004) and thus the degree of homeostasis may be highly relevant to fitness and to a species' ecological strategy on the one hand (Frost et al, 2005) and to recycling processes of superfluous material on the other one (Meunier et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Whether this lack of response resulted from the shorter duration of our experiment (14 days for Physella; c.f. Stelzer and Lamberti (2002); Fink and Von Elert (2006); Ohta et al (2011)] or due to herbivore behavioural or physiological adjustments, through selective feeding or increased assimilation efficiency for the limiting nutrient (Frost et al 2005;Hessen et al 2013), warrants further research. Nevertheless, Liess and Hillebrand (2005) showed that some herbivores can adjust their metabolism in response to changes in periphyton nutrient concentration during a 14-day experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Organisms might compensate nutrient deficiences by increasing ingestion (i.e. compensatory feeding), thus maintaining their homeostasis and growth (Frost et al 2005;Fink and Von Elert 2006;Flores et al 2014). Nevertheless, reduced microbial conditioning and food quality have also been observed to dampen detritivore ingestion rates when fed on low quality leaves (Aßmann et al 2011;Danger et al 2012;Graça and Poquet 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A growing body of evidence suggests, however, that intraspecific variability in organismal stoichiometry is greater than was previously thought (Bertram et al, 2008;El-Sabaawi et al, 2012a,b;González et al, 2011;Small et al, 2011). Therefore, consumer body stoichiometry can often track diet or environmental stoichiometry (Frost et al, 2005b;Goloran et al, 2015;Schade et al, 2003Schade et al, , 2005. For example, zooplankton C:P ratio is strongly correlated to the seston C:P ratio (Hessen et al, 2005).…”
Section: Introductionmentioning
confidence: 98%